Multivariate analyses of supposedly duplicate accessions of east African highland bananas in germplasm colections in Uganda - Pickersgrill, B.; Vuylsteke, D.R.; Gold, C.; Karamura, E.B.; Kiggundu, A.; Karamura, D. (2000)
Thirty-seven pairs of accessions of East African highland bananas, listed under the same name in the Ugandan germplasm collections at Kawanda and Kabanyolo, were surveyed for 50 morphological characters. The data were subjected to cluster analysis and principal components analysis. Duplicates known to be ramets of a single clone were more similar than duplicates that simply shared the same name. Accessions did not separate into Kawanda-grown and Kabanyolo-grown groups, so differences in growing conditions at the two sites, although producing differences in phenotype, did not distort seriously the similarities and differences among the accessions. The analyses also detected examples of human error (mislabelling or mixing of suckers), and of one local name being used for more than one clone. The analyses sorted the accessions into groups which agreed in general with an independent subjective classification.